Предмет:
МатематикаАвтор:
аноним1) √2x^2 + 4√3x - 2√2 = 0;
x12 = (-4√3 +- √16 * 3 - 4 * √2 * (-2) * √2) / √2 = (-4√3 +- 4√3) / √2;
x1 = (-4√3 + 4√3) / 2√2 = 0; x2 = (-4√3 - 4√3) / 2√2 = -4√3/2.
2) y^2 + 2(√3 + 1)y + 2√3 = 0;
y12 = (-2(√3 + 1) +- √(4 * (√3 + 1)^2 - 4 * 2√3) / 2 = (2(√3 + 1) +- 2) / 2 ;
y1 = √3 + 1 - 1 = √3; y2 = √3 + 1 + 1 = √3 + 2.
Автор:
kylerhsbpДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть